Energy consumption, energy savings and emission analysis for industrial motors - Saidur, R.; Hasanuzzaman, M.; Rahim, N.A. (2010)
Energy is one of the indispensable factors for continuous development and economic growth. The industrial sector is the largest user of energy in Malaysia. Since motors are the principle energy users, different energy savings, strategies have been applied to reduce their energy consumption and associated emissions released into the atmosphere. These strategies include using high efficient motors and Variable Speed Drive (VSD). It has been estimated that there can be a total energy savings of 1765MWh, 2703 MWh and 3605MWh by utilizing energyefficient motors for a 50%, 75% and 100% load respectively. Similarly, it is hypothesized that a significant amount of energy can be saved using VSD to reduce speed, thus cutting energy costs. Moreover, a substantial reduction in the amount of emissions can be effected together with the associated energy savings for different energy savings strategies. It is clear that the use of VSDs and energy efficient motors leads to substantial energy savings and an enormous reduction in emissions.